Vallecular Cysts in Adult Population: Ten Year Experience - Singhal, Surinder K; Verma, Hitesh; Dass, Arjun; Punia, Rajpal (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10152 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 5-7